(untitled) (LEARNing Landscapes, 2022)
This paper describes the pedagogical roots of the work we do, both as teachers and as performers; and how our work reaches beyond the classroom and into community, eliciting narratives and weaving them through improvised dance and music collaborations, eventually onto the walls of an art museum. Our concept was to solicit stories that told of some event that happened in a particular place, and that left a memory that was tethered to that place. We collected stories, pooled our own stories, “pinned” stories to their geographic locations, and then transformed these stories through improvised movement and sound.